Impact of Using Technology in Teaching English Language - Mohamed, Rashid Hasan Taha (Journal of Educational and Psychological Sciences, 2022)
The present study aimed at investigating to what extent teachers use technological devices and (as general) in the department of English Language in Hasahiesa Joint School. The study aims to identify which factors contribute to, or discourage teachers use of technology in English Language teaching. It also focuses on the actual role played by English language teachers. Descriptive, analytical and experimental methods are used to test quantitatively and qualitatively the collected data. Data are collected through two research instruments, namely, a test (pre/ post test) and two questionnaires at the end of the experiment to elicit the subjects attitudes towards technology. One questionnaire is directed to the teachers (30 teachers) and the other is directed to the students (52 students who are divided into two homogeneous groups after the first test). Intervention interwoven with the regular teaching by research is conducted. The quantities and qualitative data are statistically analyzed by using the (SPSS). According to the questionnaire results, It is clear that the students have positive attitudes towards such learning. The results also show the mere introduction of computer technology resources. Consequently, the provision of training which is the key factor in both changing attitudes and encouraging teachers to incorporate technology in their instruction is highly recommended.